Studies in Baccharidinae (Asteraceae: Astereae). I: Lanugothamnus a new genus from South America - Deble, Leonardo Paz (Balduinia, 2014)
It is described a new genus of Asteraceae, named Lanugothamnus, to include eighteen species and one subspecies of Baccharis before placed in the subgenus Tarchonanthoides. The genus Lanugothamnus has discussed its infragenerical treatment, being segregated in four subgenera: Lanugothamnus, Toxicothamnus, Curitybenses, and Tarchonanthoides. The subgenus Toxicothamnus is a taxonomic novelty, while the subgenera Curitybenses and Tarchonanthoides are based in Baccharis sect. Curitybenses, and Baccharis subg. Tarchonanthoides, respectively. Two new sections are described: Sericicarpa and Pluricephala. The former belongs to subgenus Lanugothamnus, while the later belongs to subgenus Toxicothamnus. Furthermore, two new species, named Lanugothamnus Anabelae and L. pluricapitulatus are described, illustrated and have their taxonomic affinities discussed. Lectotypes are proposed to names Baccharis artemisioides, B. patens, and B. squarrosa. Baccharis multipaniculata is placed in synonymy with Lanugothamnus scabrifolius. A key to segregate the subgenera and species of Lanugothamnus is given, and the appropriate new combinations are made.